O gênero senna mill. (leguminosae, caesalpinioideae, cassieae) na região centro-oeste do Brasil, com ênfase nas espécies ocorrentes no estado de Goiás - Santos, Josimar Pereira (2013)
Leguminosae is cosmopolitan and the third largest family of flowering plants with about 727 genera and 19,325 species allocated in the subfamilies Mimosoideae, Papilionoideae and Caesalpinioideae. In Brazil, this family, is the most diverse with approximately 171 genera and 2,694 species, although it is poorly studied. Caesalpinioideae stands out by systematic controversial of the majority of its taxa, as Chamaecrista, Cassia and Senna members of the tribe Cassieae subtribe Cassiinae subtribe. Senna with 350 species, 280 of which American, is a monophyletic genus and very little known taxonomically, especially in Brazil, where it is represented by 80 species. Motivated by the limited taxonomic knowledge of the Brazilian species of Senna and the attractive and intriguing morphology of its taxa, this dissertation aimed to: 1) to perform a taxonomic synopsis of the genus Senna in the Midwest Region, in order to elucidate its diversity in the region in question, as well as subsidizing floristic and taxonomic study considering the family Leguminosae, and 2) to execute a taxonomic study of the species Senna occurring in Goiás aiming to contribute to the systematic of the genus, as well as, with the knowledge of floristic diversity of the Goiás state. Both studies were based on usual methods in plant taxonomy. In the first study were found 75 taxa belonging to 36 species, four subspecies and 35 varieties, with Mato Grosso and Goiás with 26 and 25 species respectively, the states where the genus showed more rich, followed by Mato Grosso do Sul and District Federal District with 23 and 18 species each. In the second study we have found 25 species, 4 subspecies and 22 varieties, being Senna pilifera var. tubata, S. silvestris var. guaranitica, S. splendida var. splendida and S. splendida var. gloriosa new records to the state, while S. latifolia and S. spinescens although cited for Goiás, were excluded of this study because their distributions correspondig with the current limits of the State of Tocantins. For both studies are presented identification key, illustrations with diagnostic characters for recognizing of the taxa, and comments about ecology and geographical distribution of the same. In addition, in the second study, are provided comments about morphological relationships among taxa.